Impact of Global DNA Methylation in Treatment Outcome of Colorectal Cancer Patients - Fouad, Mariam A.; Salem, Salem E.; Hussein, Marwa M.; Zekri, Abdel Rahman N.; Hafez, Hafez F.; El Desouky, Eman D.; Shouman, Samia A. (Frontiers in Pharmacology, 2018)
Background: Global DNA methylation has an impact in cancer pathogenesis and progression. This study aimed at investigating the impact of global DNA methylation in treatment outcome of colorectal (CRC) patients. Patients and methods: Global DNA methylation was measured by LC/ MS/ MS in whole blood of 102, 48 and 32 Egyptian CRC patients at baseline and after 3 & 6 months of FP therapy respectively, in addition to 32 normal healthy control. The genetic expressions of DNA methyltransferases (DNMTs) were determined. Survival analysis was performed at all clinicopathological and molecular subgroups of patients. Results: Egyptian CRC patients are characterized by early onset disease and high prevalence of rectum cancer. At baseline, they had significant global hypomethylation of 5mC level and 5mC % with overexpression of DNMT3A and 3B. Significant higher 5mC levels were shown in patients > 45 years, males, with T2 tumors, stage II, negative lymph nodes, and negative metastasis. FP therapy caused a significant reduction in DNA methylation particularly in the subgroups of patients with high DNA methylation at a baseline level and good prognostic features. After 3 years of follow up, patients with 5mC % > 8.02 % had significant deterioration in overall survival (OS) and significant positive impact in event-free survival (EFS) was associated patients with 5mC level > 0.55 and T2 tumors. Hazards of death and progression were significantly associated patients with high initial CEA level and positive metastasis. Conclusions: Global DNA methylation has a significant impact on the survival and treatment outcome of Egyptian CRC patients treated with FP- based therapy.